Penatalaksanaan art therapy terhadap kecemasan dan stres ibu hamil: A literature review - Meiranny, Arum; Kusumaningsih, Meilia Rahmawati; Listi, Fera Ratna (Holistik Jurnal Kesehatan, 2025)
Background: Pregnant women often face psychological challenges, such as anxiety and stress, which can negatively impact maternal health and fetal development. One alternative approach to managing anxiety and stress is art therapy, which enables pregnant women to express emotions creatively to enhance psychological well-being. Purpose: To evaluate the effectiveness of art therapy in managing anxiety and stress in pregnant women. Method: A literature review was conducted by accessing sources from Google Scholar, PubMed, and ScienceDirect. A total of 10 selected articles, consisting of 6 international journals and 4 national journals published within the last 10 years, were analyzed. The included studies focused on the implementation of art therapy to reduce anxiety and stress in pregnant women. Results: The analysis of several studies revealed that art therapy has a significant effect on reducing anxiety and stress levels among pregnant women. This therapy provides positive psychological and emotional benefits by creating opportunities for relaxation and self-expression. Conclusion: Art therapy is effective in reducing anxiety and stress among pregnant women. This knowledge can be utilized by healthcare professionals as a non-pharmacological intervention to improve the mental health of pregnant women during pregnancy.   Keywords: Anxiety; Art Therapy; Pregnancy; Stress.   Pendahuluan: Ibu hamil sering menghadapi tantangan psikologis, seperti kecemasan dan stres, yang dapat berdampak negatif pada kesehatan ibu serta perkembangan janin. Salah satu pendekatan alternatif untuk mengatasi kecemasan dan stres adalah melalui art therapy, yang memungkinkan ibu mengekspresikan emosi secara kreatif guna meningkatkan kesejahteraan psikologis. Tujuan: Untuk mengevaluasi penatalaksanaan art therapy terhadap kecemasan dan stres ibu hamil. Metode: Kajian literatur dilakukan dengan mengakses sumber dari Google Scholar, PubMed, dan ScienceDirect. Sebanyak 10 artikel terpilih, terdiri dari 6 jurnal internasional dan 4 jurnal nasional yang diterbitkan dalam 10 tahun terakhir, digunakan sebagai dasar analisis. Penelitian yang disertakan mencakup penatalaksanaan art therapy untuk mengurangi kecemasan dan stres pada ibu hamil. Hasil: Analisis dari beberapa penelitian menunjukkan, bahwa art therapy secara signifikan berpengaruh dalam menurunkan tingkat kecemasan dan stres pada ibu hamil. Terapi ini memberikan manfaat positif, baik secara psikologis maupun emosional dengan menciptakan ruang untuk relaksasi dan ekspresi diri. Simpulan: Art therapy efektif dalam menurunkan kecemasan dan stres pada ibu hamil. Pengetahuan ini dapat dimanfaatkan oleh tenaga kesehatan sebagai bagian dari intervensi non-farmakologi untuk meningkatkan kesehatan mental ibu selama kehamilan.   Kata Kunci: Art Therapy; Ibu Hamil; Kecemasan; Stres.